THE APPLICATION OF DECISION SUPPORT SYSTEM TO IDENTIFY CHILDREN WITH INTELLECTUAL DISABILITIES - Abdul Salim; Munawir Yusuf; Gunarhadi Gunarhadi (Proceedings of The ICECRS, 2016)
The research is intended to measure the accuracy of Decision Support System (DSS) to identify the characteristics of children with intellectual disabilities. A number of 40 teachers in Central Java, Indonesia were assigned as the sample comprising 16 special school teachers and 4 inclusive school teachers. As respondents, these teachers are required to (a) have a training on sofware application of DSS program of identification instrument, (b) have an experience on using DSS program, (c) have full commitment to the research activity. The data was collected from questionnaire and analized by quantitaive description. The reseacrh concluded that DSS program indicated the accuracy of 99,8%, and as many as 92.5% of teachers commented that DSS program was easy to use for identification of children with intellectual disabilities.